Analysis of the Relationship between Physical Education Teacher Candidates’ Academic Life Satisfaction and Their Beliefs in Teaching Profession: A Study on Physical Education and Sports Teachers (Sample of the Mediterranean Region) - Erkan Çimen (Journal of Educational Issues, 2024)
In this study, it was aimed to examine the relationship between physical education and sports teacher candidates’ academic life satisfaction and their beliefs in the teaching profession. The population of the research consisted of 1482 physical education and sports teacher candidates studying in the Mediterranean region. The sample group consisted of 318 teacher candidates who participated in the study in this universe. Volunteers were asked to fill in the personal information form, the academic life satisfaction and professional belief scales. It was decided to apply non-parametric tests in the statistical analysis of the data obtained. Spearman correlation analysis was applied to reveal the relationships between the scores obtained from the scales. As a result; it was determined that the academic life satisfaction levels of the teacher candidates were above the average, and the average of the scores they got from the total professional belief scale and the sub-headings of the scale were found to be high. It was found that there is a moderate relationship between academic life satisfaction and professional beliefs. It is thought that the results of the present study are due to the fact that physical education and sports teacher candidates learn the sportive knowledge and skills that may be necessary in their future profession, theoretically and practically, at the highest efficiency level in the undergraduate programs they study, and that they can actively apply this knowledge and skills in the field with different internship applications.